Hadith and Women’s Voices: A Critical Analysis of Amina Wadud’s Methodology in Interpreting Gender Bias - Sahid Hadi Kusuma; Khairuddin Akhyar; Ahmad Multazam; Muh Imran; Sawaluddin Jamardi (Arba: Jurnal Studi Keislaman, 2026)
The study of hadith in the classical tradition often reflects interpretive patterns shaped by patriarchal constructions, thus marginalizing women’s experiences and voices from religious authority. The lack of methodological studies on the application of Amina Wadud’s feminist hermeneutics to a corpus of hadith considered gender-biased indicates a significant academic gap that needs to be addressed to achieve a more just and inclusive discourse on interpretation. This study aims to describe Wadud’s methodological steps in reading hadith; evaluate her strengths and limitations in interpreting gender-problematic texts; and examine their theoretical and practical implications for the development of hadith studies from a gender-justice perspective. The research method employed is qualitative with a critical-hermeneutical analysis approach, through reading gender-problematic hadith. The results show that Wadud positions gender bias as a historical construct born of patriarchal culture during the period of hadith transmission. She emphasizes the distinction between universal normative texts and culturally contextual interpretations. Using the ethical hermeneutic strategy of the Quran, Wadud reinterprets hadiths on leadership and witnessing, emphasizing egalitarian principles that reject the subordination of women. This approach demonstrates the potential for a more participatory and responsive reinterpretation of the text in the pursuit of gender justice. However, its limitations lie in the potential for interpreter subjectivity and resistance from traditionalists. In conclusion, Wadud’s methodology makes a significant contribution to the development of more contextual, critical, and ethical gender-based interpretations of hadith.